2022
DOI: 10.1002/ana.26338
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Rodent Thalamus and Corpus Callosum in Seizure Generalization

Abstract: Objective Bilateral synchronous cortical activity occurs during sleep, attention, and seizures. Canonical models place the thalamus at the center of bilateral cortical synchronization because it generates bilateral sleep spindle oscillations and primarily generalized absence seizures. However, classical studies suggest that the corpus callosum mediates bilateral cortical synchronization. Methods We mapped the spread of right frontal lobe‐onset, focal to bilateral seizures in mice and modified it using chemo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The mediating role of the thalamus in cortico-cortical communication in seizures that secondarily generalise has been analysed in rodent [52] and human [53, 11] studies. Reduced basal ganglia–thalamus network interaction is suggested to increase the propensity for secondary generalisation [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…The mediating role of the thalamus in cortico-cortical communication in seizures that secondarily generalise has been analysed in rodent [52] and human [53, 11] studies. Reduced basal ganglia–thalamus network interaction is suggested to increase the propensity for secondary generalisation [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…We also suppressed the right motor thalamic nuclei using chemo- and closed-loop optogenetics and lesioned the corpus callosum. 24 Suppression of the motor thalamus did not prevent bilateral spread, whereas callosal lesioning abolished secondary generalization. Using viral tracing, we found that the right and left thalami have minimal direct monosynaptic commissural connections, whereas the callosum sends extensive contralateral projections that are transmitting seizures.…”
Section: Secondary Bilateral Synchrony During Seizuresmentioning
confidence: 98%
“…31 To disentangle the roles of the thalamus and callosum in bilateral seizure spread, we recorded local field potentials (LFPs) from the bilateral premotor cortex and ventrolateral motor thalamus simultaneously to map their temporal sequence of activation. 24 We selected the motor thalamus because it receives strong projections from the right motor cortex, the seizure focus in our case. 32 Seizures that originated in the right premotor cortex reached the left premotor cortex faster than they did the left thalamus.…”
Section: Secondary Bilateral Synchrony During Seizuresmentioning
confidence: 99%
“…In this paper, Brodovskaya and colleagues explore pathways by which focal seizure activity spreads to the opposite hemisphere, causing a GTC. 2 The investigators injected cobalt (Co 2+ ), a proconvulsant divalent cation, into the right frontal cortex of C57Bl/6 mice to create a seizure focus. Seizure activity in the form of epileptic local field potentials (LFPs) was then monitored as it progressed to nearby and distant sites.…”
Section: Commentarymentioning
confidence: 99%